Implementasi Sistem Informasi Akademik di TK Kabupaten Bireuen Studi Kasus Pada TK Sabir : Penelitian - Nurma; Aminah; Said Mulyadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the implementation of academic information systems in improving administrative services at Sabir Bireuen Kindergarten. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study indicate that the planning of system implementation is carried out through needs analysis, preparation of simple computer-based application devices, and training of administrative staff. The implementation of the academic information system at Sabir Kindergarten is effective in managing student data, financial administration, and activity schedules. Evaluations are carried out periodically by the principal to ensure optimal use of the system. The implementation of this academic information system has been proven to facilitate administrative services and increase the speed of academic data services.